Website Quality Evaluation of Engineering Faculty Using IPA-WebQual 4.0: A Mixed-Methods Approach for User-Centered Redesign - Aldiyanto Gunawan; Kurniawan Hamidi (Journal of Digital Ecosystem for Natural Sustainability, 2026)
University faculty websites serve as the primary medium of academic communication, information dissemination, and institutional branding. Suboptimal website quality directly undermines user satisfaction and institutional credibility. This study evaluates the Faculty of Engineering website at Universitas Universal using the Importance-Performance Analysis (IPA) method integrated with the WebQual 4.0 framework, encompassing usability, information quality, and service interaction quality dimensions. A quantitative survey was conducted involving 30 purposively selected respondents (active students, lecturers, administrative staff, and alumni) who had accessed the website within the preceding six months. Instrument validity was confirmed through corrected item-total correlation (r > 0.361) and reliability via Cronbach's Alpha (α = 0.936 and 0.938 for performance and importance dimensions, respectively). IPA analysis positioned 14 attributes within a Cartesian quadrant matrix, revealing that four critical attributes fell in Quadrant I (high importance, low performance): internship opportunity information, job vacancy information for alumni, current engineering articles, and visual identity. The overall conformity level was 65%, indicating a significant performance-expectation gap. Based on these findings, three alternative website redesign concepts were developed using Odoo Website Builder, addressing the priority improvement areas. The proposed design incorporates modern UI principles (Poppins typography, card-based layouts, segmented content architecture) and new functional pages for career development. This study contributes a replicable IPA-WebQual evaluation framework applicable across higher education digital platforms.